Techno-Sharia in the Age of Intangible Assets: Digital Inheritance of Metaverse Property - Muntazar, Ahmad; Syafruddin, Syafruddin; Bariyah, Oneng Nurul; Larhzizer, Fouad (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2026)
The emergence of intangible digital assets within the Metaverse, notably Non-Fungible Tokens (NFTs) adhering to the ERC-721 and ERC-1155 standards, presents significant challenges to Islamic inheritance law (farāʾiḍ), which has traditionally been predicated on tangible notions of property. Situated within the nascent discourse of Techno-Sharia, this study undertakes a reconstruction of the classical concept of māl (property) to ascertain the legal status and inheritability of such digital assets. Utilizing a qualitative, library-based methodology, the research employs a taḥlīlī (analytical) and muqāran (comparative) fiqh approach to deconstruct juristic criteria of māl and apply them to blockchain-based assets. The findings indicate that Metaverse assets satisfy the three fundamental conditions of māl: recognized market value (al-taqawwum), permissible utility (al-manfaʿah), and exclusive control through cryptographic ownership, which functions as a contemporary analogue to al-ḥiyāzah (possession). Accordingly, these assets qualify as part of the tirkah (inheritable estate). Nonetheless, their inclusion introduces considerable challenges for the implementation of farāʾiḍ, including inaccessible wallets resulting from lost private keys (rendering assets māl dāʾiʿ), valuation volatility (taqwīm), indivisibility (qismah), and conflicts between immutable smart contracts and Sharia-based distribution principles. This study proposes the adoption of fractionalized NFTs (fNFTs) and the development of Sharia-compliant smart contracts to ensure accessibility, validity, and justice in digital inheritance practices.